2018
DOI: 10.1002/acm2.12310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical acceptance testing and scanner comparison of ultrasound shear wave elastography

Abstract: Because of the rapidly growing use of ultrasound shear wave elastography (SWE) in clinical practices, there is a significant need for development of clinical physics performance assessment methods for this technology. This study aims to report two clinical medical physicists’ tasks: (a) acceptance testing (AT) of SWE function on ten commercial ultrasound systems for clinical liver application and (b) comparison of SWE measurements of targets across vendors for clinical musculoskeletal application. For AT, ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…An additional plausible explanation is that the phantoms' elastic integrity may change over time through inappropriate storage or aging of the hydrogel material. Long et al [ 35 ] recently suggested using elasticity phantoms for acceptance testing only (i.e., to verify that the new SWE machine is acquiring the same readings as another similar machine from the same manufacturer).…”
Section: Discussionmentioning
confidence: 99%
“…An additional plausible explanation is that the phantoms' elastic integrity may change over time through inappropriate storage or aging of the hydrogel material. Long et al [ 35 ] recently suggested using elasticity phantoms for acceptance testing only (i.e., to verify that the new SWE machine is acquiring the same readings as another similar machine from the same manufacturer).…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that SWS measurements depend on the measurement system 1,2,6,7,8 . These system differences cause clinical uncertainty and slow the adoption of this technology by the clinical community.…”
mentioning
confidence: 99%
“…The reliability of SWE measurements differs across muscles (Davis et al, 2019) and may depend on the size and positioning of the region of interest (Alfuraih et al, 2018). Inter‐system reliability is not granted (Javed et al, 2022; Long et al, 2018; Mulabecirovic et al, 2016). The reliability of SWE measurements should be documented for the conditions of the study (Alfuraih et al, 2017).…”
Section: Discussionmentioning
confidence: 99%